The Relationship of Mom's Knowledge about the Importance of Measles Rubella (MR) Immunization with Compliance with Immunization - Aswan, Yulinda; Farida Utaminingtyas; Helmy Apreliasari; Yusnina Maysaroh; Teti Kurniasih (International Journal of Public Health Excellence (IJPHE), 2022)
Measles and Rubella are kinds of infectious diseases through the airway that cased by virus of measles and Rubella (MR) and the immunization of measles and rubella (MR) will be one immunization to avoid the disease . This research is taken to know the correlation of mothers knowledge about Measles and Rubella Immunization in Hospitalized local government clinic of Gunungtua, North Padang Lawas Regency in the year 2021. Type of this research is quantitative research with descriptive correlation design and it is taken by cross sectional study approaches. This research is taken place at the local Government clinic unit Hospitalized Gunungtua, North Padang Lawas Regency. The population and sample of this research are coming from the mothers who have child on 9 months age until <15 old years, that are about 122 people. The results of this research show that got about p-value 0.000 <0.05, Its means that there is a significant correlation between knowledge with subservience in having Immunization of Measles Rubella (MR) int the Local Government Clinic Unit Hospitalized Gunungtua, North Padang Lawas Regency. The suggestions is the Healthy servant should give information as well as education for the society about the immunization of Measles Rubella (MR).